Strategi Marketing Public Relations Melalui media online dalam mempromosikan produk Helipad - Rosyada, Amrina (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to look further at how the product promotion strategy is carried out by Helipad. id through online media as part of marketing public relations. The paradigm used is constructivism. The method used is qualitative with a phenomenological research approach. The research results are in the form of three things. First, the online media used by Helipad.id is in the form of two parts, namely e-commerce and social media. The e-commerce used by Helipad.id is Tokopedia, Shopee, and Lazada. The social media used by Helipad.id are Instagram and Tiktok. The selection of Helipad.id online media has adjusted the target market, namely: teenagers – adults. Second, the importance of using online media in promoting Helipad.id products is building brand identity and brand awareness. The tendency of consumers to shop online compared to offline is an important point for Helipad.id to continue to carry out promotional activities through online media. In addition, customers have easy access to information obtained through online media. Finally, the use of Helipad.id social media in the context of product promotion focuses on the Instagram application. Instagram @helipad.id uses the caption & hashtag features (#hlpd, #weirdworld, and #OOTDBarengHlpd) and uploads images / videos every day which is integrated with Facebook. Helipad.id maximizes promotional strategies (promotion-mix) on Instagram and all e-commerce owned. The advertising promotion strategy is focused on Instagram social media and all Helipad.id ecommerce. Sales promotion strategies in the form of e-commerce coupons/discounts, outfit of the day (OOTD) contest prizes, as well as holding endorsements with several fashion content creators. The public relations promotion strategy is focused on the interaction of comment columns on social media and e-commerce review pages.